"LETTER TO THE KING" BY JULES DESTRY: FROM SEPARATISM TO UNITARISM IN BELGIUM - E. V. Ermakova (Vestnik MGIMO-Universiteta, 2016)
Contradictions between the regions of Belgium - Wallonia and Flanders - have a long history associated with uneven political, economic and cultural development of the territories, which in 1830 became parts of an independent state, the Kingdom of Belgium. The "Letter to the King", written by eminent Belgian politician and writer, socialist Jules Destree (1863 - 1936 gg.), is one of the most interesting sources on the history of Belgium of this period, It became a kind of manifesto of balance between the ideas of separatism and unitarianism. This article includes excerpts from the "Letter to the King", which were given for the first time in the author's Russian translation and conducted historical criticism of the source. The study is based on a set of scientific methods and approaches, including the principle of scientific objectivity and systematic approach, used in historical research. The main methods are problematic and historical-comparative analysis, classification and comparison of political and historical concepts. An external source of criticism included information about the place and the time of the creation of document, the biography of the author studies; internal critic source recreates the idea of the letter and the background of historical events. Prominent Belgian politician and writer, socialist Jules Destree (1863 - 1936), highly appreciated the personal qualities of King Albert I, appealed to his experience and political vision, describing all the problems Walloons faced in their opposition to the Flemish. Destree in his letter opposed the unequal development of the regions of Belgium and the protectionist policies of the central government in respect to the detriment of Flanders Wallonia. He summarized and formulated the factors that, in his opinion, interfere with the full development of his country. Destree pays great attention to linguistic differences, which were at the heart of conflicts between Walloons and Flemings, and are still shaken by Belgium. He reflects on the fact that the central government should be doing to reduce the national tensions that unites two people, and that the shares, which should be a system of education that future generations were able to overcome the historical alienation of such geographically close and ideologically distant peoples. Although Jules Destree firmly defends separatism idea for Wallonia as the only solution to the problem, however, by the end of his letter, reasoning it takes a more balanced position. The idea of a unitary state was not denied completely, but Destree emphasizes the importance of a balanced central government policy in relation to the regions in order to reduce internal tensions between the two nations. The ideas embodied in his "Letter to the King", formed the basis of the principles of peaceful co-existence of further autonomous regions as part of the union, which was manifested in the future during the First World War, when the Walloons and Flemings alongside confronted a common enemy.